2020
DOI: 10.4103/ams.ams_154_19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-rich plasma and concentrated growth factor in treating androgenetic alopecia - A retrospective study

Abstract: Introduction: Plasma derivatives have been practiced a lot in orthopedics, burns, and sport medicine. Microneedling (MN) with platelet-rich plasma (PRP) therapy has been proven to improve the micro-circulation and thus improve hair growth. The role of concentrated growth factor (CGF) for hair growth has not been mentioned anywhere in the literature for hair growth which we tried to prove in our article by comparing it with various other studies. Materials and Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…18 The hair pull test also showed a pronounced improvement as compared to the baseline result of the same which is comparable to the study performed by Steward and coworkers, in which only one (5%) out of 20 patients had an increase in hair fall in the hair pull test as compared to the results of the hair pull test done preoperatively. 19 Scalp pain during injections was the most common adverse event reported in the present study, which was related to injection pricks, followed by erythema and scalp irritation during healing. All these adverse events were found to be mild and well tolerated by the patients.…”
Section: Discussionmentioning
confidence: 56%
“…18 The hair pull test also showed a pronounced improvement as compared to the baseline result of the same which is comparable to the study performed by Steward and coworkers, in which only one (5%) out of 20 patients had an increase in hair fall in the hair pull test as compared to the results of the hair pull test done preoperatively. 19 Scalp pain during injections was the most common adverse event reported in the present study, which was related to injection pricks, followed by erythema and scalp irritation during healing. All these adverse events were found to be mild and well tolerated by the patients.…”
Section: Discussionmentioning
confidence: 56%
“…8 The growth factor content in CGF and adhesion and stretch of fibrin are better than those in PRP. 9 Steward et al 10 found that PRP combined with microneedles and CGF gel can improve microcirculation and promote hair growth in 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The growth factor content in CGF and adhesion and stretch of fibrin are better than those in PRP 9 . Steward et al 10 found that PRP combined with microneedles and CGF gel can improve microcirculation and promote hair growth in 20 patients. Tan et al 11 found that when one side of the scalp was injected with CGF, the other side was injected with placebo, and minoxidil was used 3 months after injection, it was observed that the hair density and hair growth rate of CGF injection side were significantly higher than those of minoxidil group alone, which indicated that CGF combined with minoxidil might be better in the treatment of alopecia.…”
Section: Discussionmentioning
confidence: 99%
“…Steward et al 50 reported a new therapy combining microneedling, PRP, and CGF without using any other drugs or laser therapy to treat androgenetic alopecia (AGA) of 20 male patients. The venous blood was extracted for preparation of PRP liquid and CGF gel.…”
Section: Cgf Applications In Hair Lossmentioning
confidence: 99%